Irreversible Conductive Filament Contacts for Passivated van der Waals Heterostructure Devices. (5th August 2022) - Na, Youn Sung; Shin, June‐Chul; Ji, Eunji; Huh, Woong; Im, Inhyuk; Watanabe, Kenji; Taniguchi, Takashi; Jang, Ho Won; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract: 2D materials with atomic‐scale thickness have attracted immense interest owing to their intriguing properties, which can be useful for electronic devices. As ultrathin 2D materials are highly vulnerable to external conditions, passivation of 2D materials is required to maintain the stability of 2D electronic devices. However, 2D channels are embedded in passivation layers, making the formation of suitable contacts in passivated 2D devices challenging. Here, a novel method for fabricating irreversible conductive filament (ICF) contacts on a 2D channel passivated by hexagonal boron nitride (hBN) layers is demonstrated. Defective paths are formed in the top hBN layer of hBN‐encapsulated graphene (or MoS2 ) using oxygen‐plasma treatment, along which ICFs are fabricated by applying repetitive bias. ICF contacts formed in the combined paths of migrated metal atoms and vacancies are stable during device operation, which is in contrast with that the filaments in hBN memristors are reversible. Field‐effect transistors with ICF contacts exhibit a low contact resistance and high stability. This study shows a new contact method, which has great potential for high‐performance 2D electronics devices. Abstract : This study shows an irreversible conductive filament (ICF) contact on a 2D channel passivated by hexagonal boron nitride. Using oxygen‐plasma treatment, defects form permanent conductive paths by the migration of metal ions and vacancies, generating ICFs through the defective paths to form contacts with the embedded 2D channel layer. So ICF contact can be of immense potential for use in high‐performance 2D electronic devices.